Deep learning approach to detect and visualize sexual dimorphism in monomorphic species - Nicolas J. Silva; André C. Ferreira; Liliana R. Silva; Samuel Perret; Sonia Tieo; Julien P. Renoult; Rita Covas; Claire Doutrelant (Animal Behaviour, 2025)

Spatial distribution of selenium-mercury in Arctic seabirds - Marta Cruz-Flores; Jérémy Lemaire; Maud Brault-Favrou; Signe Christensen-Dalsgaard; Carine Churlaud; Sébastien Descamps; Kyle Elliott; Kjell Einar Erikstad; Alexey Ezhov; Maria Gavrilo; David Grémillet; Gaël Guillou; et al. (Environmental Pollution, 2024)

A keystone avian predator faces elevated energy expenditure in a warming Arctic - Melissa L. Grunst; Andrea S. Grunst; David Grémillet; Akiko Kato; Paco Bustamante; Céline Albert; Émile Brisson‐Curadeau; Manon Clairbaux; Marta Cruz‐Flores; Sophie Gentès; Antoine Grissot; Samuel Perret; et al. (Ecology, 2023)
Climate change is transforming bioenergetic landscapes, challenging behavioral and physiological coping mechanisms. A critical question involves whether animals can adjust behavioral patterns and energy expenditure to stabilize fitness given reconfiguration of resource bases, or whether limits to plasticity ultimately compromise energy balance. In the Arctic, rapidly warming temperatures are transforming food webs, making Arctic organisms strong models for understanding biological implications of climate change‐related environmental variability. We examined plasticity in the daily energy expenditure (DEE) of an Arctic seabird, the little auk ( Alle alle ) in response to variability in climate change‐sensitive drivers of resource availability, sea surface temperature (SST) and sea ice coverage (SIC), and tested the hypothesis that energetic ceilings and exposure to mercury, an important neurotoxin and endocrine disrupter in marine ecosystems, may limit scope for plasticity. To estimate DEE, we used accelerometer data obtained across years from two colonies exposed to distinct environmental conditions (Ukaleqarteq [UK], East Greenland; Hornsund [HS], Svalbard). We proceeded to model future changes in SST to predict energetic impacts. At UK, high flight costs linked to low SIC and high SST drove DEE from below to above 4 × basal metabolic rate (BMR), a proposed energetic threshold for breeding birds. However, DEE remained below 7 × BMR, an alternative threshold, and did not plateau. Birds at HS experienced higher, relatively invariable SST, and operated above 4 × BMR. Mercury exposure was unrelated to DEE, and fitness remained stable. Thus, plasticity in DEE currently buffers fitness, providing resiliency against climate change. Nevertheless, modeling suggests that continued warming of SST may promote accelerating increases in DEE, which may become unsustainable.

Carryover effects of winter mercury contamination on summer concentrations and reproductive performance in little auks - Alice Carravieri; Sophie Lorioux; Frédéric Angelier; Olivier Chastel; Céline Albert; Vegard Sandøy Bråthen; Émile Brisson-Curadeau; Manon Clairbaux; Karine Delord; Mathieu Giraudeau; Samuel Perret; Timothée Poupart; et al. (Environmental Pollution, 2023)

An avian urban morphotype: how the city environment shapes great tit morphology at different life stages - Aude E. Caizergues; Anne Charmantier; Marcel M. Lambrechts; Samuel Perret; Virginie Demeyrier; Annick Lucas; Arnaud Grégoire (Urban Ecosystems, 2021)

Density‐dependent natural selection mediates harvest‐induced trait changes - Alix Bouffet‐Halle; Jacques Mériguet; David Carmignac; Simon Agostini; Alexis Millot; Samuel Perret; Eric Motard; Beatriz Decenciere; Eric Edeline (Ecology Letters, 2021)
Rapid life‐history changes caused by size‐selective harvesting are often interpreted as a response to direct harvest selection against a large body size. However, similar trait changes may result from a harvest‐induced relaxation of natural selection for a large body size via density‐dependent selection. Here, we show evidence of such density‐dependent selection favouring large‐bodied individuals at high population densities, in replicated pond populations of medaka fish. Harvesting, in contrast, selected medaka directly against a large body size and, in parallel, decreased medaka population densities. Five years of harvesting were enough for harvested and unharvested medaka populations to inherit the classically predicted trait differences, whereby harvested medaka grew slower and matured earlier than unharvested medaka. We show that this life‐history divergence was not driven by direct harvest selection for a smaller body size in harvested populations, but by density‐dependent natural selection for a larger body size in unharvested populations.

Pheomelanin-based coloration is related to individual quality and oxidative stress in blue petrels - Sarah Leclaire; Samuel Perret; Ismael Galván; Francesco Bonadonna (Evolutionary Ecology, 2019)

Development and implementation of eco-genomic tools for aquatic ecosystem biomonitoring: the SYNAQUA French-Swiss program - Estelle Lefrançois; Laure Apothéloz-Perret-Gentil; Philippe Blancher; Samuel Botreau; Cécile Chardon; Laura Crepin; Tristan Cordier; Arielle Cordonier; Isabelle Domaizon; Benoit J. D. Ferrari; Julie Guéguen; Jean-Christophe Hustache; et al. (Environmental Science and Pollution Research, 2018)

Short‐term prey field lability constrains individual specialisation in resource selection and foraging site fidelity in a marine predator - Nicolas Courbin; Aurélien Besnard; Clara Péron; Claire Saraux; Jérôme Fort; Samuel Perret; Jérémy Tornos; David Grémillet (Ecology Letters, 2018)
Spatio‐temporally stable prey distributions coupled with individual foraging site fidelity are predicted to favour individual resource specialisation. Conversely, predators coping with dynamic prey distributions should diversify their individual diet and/or shift foraging areas to increase net intake. We studied individual specialisation in Scopoli's shearwaters ( Calonectris diomedea ) from the highly dynamic Western Mediterranean, using daily prey distributions together with resource selection, site fidelity and trophic‐level analyses. As hypothesised, we found dietary diversification, low foraging site fidelity and almost no individual specialisation in resource selection. Crucially, shearwaters switched daily foraging tactics, selecting areas with contrasting prey of varying trophic levels. Overall, information use and plastic resource selection of individuals with reduced short‐term foraging site fidelity allow predators to overcome prey field lability. Our study is an essential step towards a better understanding of individual responses to enhanced environmental stochasticity driven by global changes, and of pathways favouring population persistence.

Nest design in a changing world: Great tit Parus major nests from a Mediterranean city environment as a case study - Marcel M. Lambrechts; Anne Charmantier; Virginie Demeyrier; Annick Lucas; Samuel Perret; Matthieu Abouladzé; Michel Bonnet; Coline Canonne; Virginie Faucon; Stéphanie Grosset; Gaëlle le Prado; Frédéric Lidon; et al. (Urban Ecosystems, 2017)

State transitions: a major mortality risk for seasonal species - Julie Landes; Martine Perret; Isabelle Hardy; Carlo Giovanni Camarda; Pierre‐Yves Henry; Samuel Pavard (Ecology Letters, 2017)
Ageing results from the accumulation of multifactorial damage over time. However, the temporal distribution of this damage remains unknown. In seasonal species, transitions between seasons are critical periods of massive physiological remodelling. We hypothesised that these recurrent peaks of physiological remodelling are costly in terms of survival. We tested whether captive small primates exposed to an experimentally increased frequency of seasonal transitions die sooner than individuals living under natural seasonality. The results show that experiencing one additional season per year increases the mortality hazard by a factor of 3 to 4, whereas the expected number of seasons lived is only slightly impacted by the seasonal rhythm. These results demonstrate that physiological transitions between periods of high and low metabolic activity represent a major mortality risk for seasonal organisms, which has been ignored until now.

UV coloration influences spatial dominance but not agonistic behaviors in male wall lizards - Mélissa Martin; Sandrine Meylan; Samuel Perret; Jean-François Le Galliard (Behavioral Ecology and Sociobiology, 2015)

Density‐dependent immunity and parasitism risk in experimental populations of lizards naturally infested by ixodid ticks - Marianne Mugabo; Samuel Perret; Beatriz Decencière; Sandrine Meylan; Jean-François Le Galliard (Ecology, 2015)
When effective immune defenses against parasites are costly and resources limited, individuals are expected to alter their investment in immunity in response to the risk of infection. As an ecological factor that can affect both food abundance and parasite exposure, host density can play an important role in host immunity and host–parasite interactions. High levels of intraspecific competition for food and social stress at high host density may diminish immune defenses and increase host susceptibility to parasites. At the same time, for contagious and environmentally transmitted parasites, parasite exposure often increases with host density, whereas in mobile parasites that actively search for hosts, parasite exposure can decrease with host density due to the “encounter‐dilution effect.” To unravel these multiple and potentially opposing effects of host density on immunity, we manipulated density of the common lizard Zootoca vivipara and measured local inflammation in response to PHA injection and levels of infestation by the tick Ixodes ricinus , a mobile ectoparasite for which we expected an encounter‐dilution effect to occur. Local inflammation strongly decreased with lizard density in adults, but not in yearlings. Tick infestation (abundance and prevalence) was negatively correlated with lizard density in both age classes. Using path analyses, we found independent, direct negative density feedbacks on immunity and parasite exposure in adults, supporting the hypothesis of energy constraints and/or physiological stress acting on immunity at high density. In contrast, for yearlings, the best path model showed that density diluted exposure to parasites, which themselves down‐regulated immune defenses in lizards. These results highlight the importance of investigating the pathways among host density, host immunity, and parasite infestation, while accounting for relevant individual traits such as age.

Direct and socially-mediated effects of food availability late in life on life-history variation in a short-lived lizard - Marianne Mugabo; Olivier Marquis; Samuel Perret; Jean-François Le Galliard (Oecologia, 2011)

Habitat quality as a predictor of spatial variation in blue tit reproductive performance: a multi-plot analysis in a heterogeneous landscape - Marcel M. Lambrechts; Samuel Caro; Anne Charmantier; Nicolas Gross; Marie-Jo Galan; Philippe Perret; Mireille Cartan-Son; Paula C. Dias; Jacques Blondel; Donald W. Thomas (Oecologia, 2004)